2010
DOI: 10.1680/geot.8.p.159
|View full text |Cite
|
Sign up to set email alerts
|

The mechanics of fibre-reinforced sand

Abstract: Fibres can be an effective means of reinforcing soils. This paper presents data from laboratory triaxial tests on quartzitic sand reinforced with polypropylene fibres. By keeping the studied composite consistent throughout the study (host sand and fibre characteristics kept constant), it has been possible to develop a framework of behaviour for the sand-fibre material, which provides a solid base for future research on fibre-reinforced soils. Data from previous work and from new tests have been analysed within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(61 citation statements)
references
References 36 publications
8
52
1
Order By: Relevance
“…This is not the case for the fibre reinforced specimens, for which the stress ratio at zero dilation and the slope of the stress-dilatancy relationship at higher rates of dilation are significantly different. Similar results have been reported by, for example, Michalowski and Cermak (2003) and Dos Santos et al (2010).…”
Section: Stress-dilatancysupporting
confidence: 91%
See 2 more Smart Citations
“…This is not the case for the fibre reinforced specimens, for which the stress ratio at zero dilation and the slope of the stress-dilatancy relationship at higher rates of dilation are significantly different. Similar results have been reported by, for example, Michalowski and Cermak (2003) and Dos Santos et al (2010).…”
Section: Stress-dilatancysupporting
confidence: 91%
“…In other words, the addition of fibres interferes with the packing of the grains. This was also observed by Michalowski and Zhao (1996), Ibraim and Fourmont (2007), who attributed it to the greater resistance to compaction in the presence of the fibres, and by Dos Santos et al (2010).…”
Section: Phase Relations and Initial Specimen Densitysupporting
confidence: 62%
See 1 more Smart Citation
“…The addition of fibres delays dilation as shown in the volumetric strain plots. This corroborates the findings of Michalowski and Cermak (2003) and Dos Santos et al (2010). Diambra et al (2013) however reported an increase in the dilation of specimens reinforced by thread-like fibres.…”
Section: Description Of Parameterssupporting
confidence: 91%
“…There is signiˆcant experimental evidence that the failure envelope of aˆbre-reinforced soil is non linear (Consoli et al, 2007a;Santos et al, 2010). In the case of a bilinear schematisation, which is often adopted to represent this non linearity, the normal stress at which the slope of the envelope changes is deˆned as a`critical normal stress' (s n, crit ) and grossly represents a change in thê bre to grain interaction mechanism.…”
Section: Introductionmentioning
confidence: 99%